Reactive thrombocytosis- etiology and its relationship with different hematological parameters, ESR, & CRP in Tuberculosis - Garg, Bhavana (Tropical Journal of Pathology and Microbiology, 2020)
Background: The measurements of platelet count, mean platelet volume (MPV), WBC are routinely available nowadays. The aim of this study was to determine age dependent aetiology and relationship of these parameters whether they were associated with the known markers of disease activity, erythrocyte sedimentation rate (ESR) and C- reactive protein (CRP) in Tuberculosis. Methods: This descriptive study was done on 500 patients with platelet count > 450,000/ μl and the cause being reactive. Platelet count, WBC, MPV, ESR, and CRP were measured at the time of hospitalization. Result: Most common cause of reactive thrombocytosis was found to be infection (28.8%), tissue damage (16.4%), iron deficiency anemia (16.2%), malignancy (9.6%), inflammation (non-tuberculosis) (9.4%), diabetes mellitus (6.4%), tuberculosis (6.0%) respectively. There was low degree of positive correlation between reactive thrombocytosis with WBC (r = 0.337, P= 0.06) and ESR (r = .277, P= >0.05). There was low degree of negative correlation between reactive thrombocytosis and CRP (r= -.131, P= >0.05). There was significant negative correlation between reactive thrombocytosis and MPV (r = -.561, P= >0.001). Conclusion: This study demonstrated a higher level of platelet count and lower MPV in all the patients having reactive thrombocytosis. The changes in these parameters (platelets count, WBC, MPV, CRP and ESR) may reflect a reaction to the inflammatory condition. Therefore, in endemic areas, the presence of such haematological peripheral blood changes may raise the suspicion of tuberculosis.